2005
DOI: 10.1007/s11146-005-0993-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Retail Sales

Abstract: We examine the distribution of sales for a retail chain in the Houston market using a spatial gravity model. Unlike previous empirical studies, our approach models spatial dependencies among both consumers and retailers. The results show that both forms of spatial dependence exert statistically and economically significant impacts on the estimates of parameters in retail gravity models. Contrary to the suggestions of (Gautschi, D. A. (1981). “Specification of Patronage Models for Retail Center Choice,” Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 24 publications
1
30
0
5
Order By: Relevance
“…While Gautschi (1981) and Eppli and Shilling (1996) found that the distance parameter was overstated, Lee and Pace (2005) found the parameter was understated. Fotheringham (1981) suggested that the parameter is a function of spatial structure.…”
Section: Implications Of the Work By Reilly And Huffmentioning
confidence: 97%
“…While Gautschi (1981) and Eppli and Shilling (1996) found that the distance parameter was overstated, Lee and Pace (2005) found the parameter was understated. Fotheringham (1981) suggested that the parameter is a function of spatial structure.…”
Section: Implications Of the Work By Reilly And Huffmentioning
confidence: 97%
“…Spatial interaction models and their application to retail site selection are described in Czech geographic literature, namely in the work of Maryáš (1983Maryáš ( , 1988, who is one of the most important authors. Lee and Pace (2005) refer to the studies by Gautschi (1981) Okoruwa et al (1988Okoruwa et al ( , 1994, as well as Eppli and Shilling (1996), which apply the Reilly gravitational model to specific cases. The results of the conducted studies vary in the importance that they attach to the factors of distance and store size.…”
Section: Site Location Factorsmentioning
confidence: 99%
“…Lee, Pace, 2005;Baray, Cliquet, 2007). Zde je nutné poznamenat, že zmiňované práce často nejsou jen produktem geografů, ale také prostorových ekonomů.…”
Section: Modelování Prostorových Interakcí Gravitační Modelyunclassified
“…Zde je nutné poznamenat, že zmiňované práce často nejsou jen produktem geografů, ale také prostorových ekonomů. Lee a Pace (2005) se např. zabývají prostorovou distribucí maloobchodního obratu mezi nákupní centra v souvislosti s jejich vzájemnou lokací na příkladě amerického Houstonu; v jiné studii Baray a Cliquet (2007) Podle účelů a zaměření našich výzkumů jsme volili jednotlivé způsoby šetře-ní i jejich kombinace (kromě dotazování přes základní školy).…”
Section: Modelování Prostorových Interakcí Gravitační Modelyunclassified